Persepsi Masyarakat Tentang Persahabatan dalam Film 5 cm (Studi Deskriptif Pada Siswa SMK Negeri 1 Barumun Padang Lawas) - Sri Rizki Kurnia Dalimunthe; Yan Hendra; Armansyah Matondang (Universitas Medan Area, 2020)
This study takes the theme of a film titled Public Perceptions of Friendship in the film 5 Cm. This study aims to look at the values that exist in the film 5 cm and to know the perception of friendship in the film 5 cm which includes the values of loyalty, struggle, sincerity, solidarity, mutual help, sacrifice and hard work. The method used in this research is descriptive method. The object of research is the public perception of the film 5 Cm with perception theory approach. To determine the number of respondents of this study using the sample population. The population in this study were students of SMK Negeri 1 Barumun Padang Lawas, amounting to 360 people throughout the class X, XI, XII Department of Computer Engineering and Networks (TKJ) of SMK Negeri 1 Barumun. And sampling techniques used in this research is purposive sampling by taking a sample of 40 people or 10% of the total population. Data collection techniques used is to spread out the questionnaire, literature study and documentation. Data analysis techniques in the study of data analysis techniques using descriptive method by describing and explaining the data obtained during the study. These results indicate that the film 5 Cm is a film that provides benefits to the community. The majority of students have a perception that tend to be positive about the values of friendship that exist in the film 5 Cm.